Leguminous Plants and Microbial Inoculation: An Approach for Biocatalytic Phytoremediation of Tebuthiuron in Agricultural Soil - Cruz, Victor Hugo; Moreira, Bruno Rafael de Almeida; Valério, Thalia Silva; Frias, Yanca Araujo; Silva, Vinícius Luiz da; Morais, Eduardo Beraldo de; Vasconcelos, Leonardo Gomes de; Tropaldi, Leandro; Prado, Evandro Pereira; Montagnolli, Renato Nallin; Lopes, Paulo Renato Matos (Agronomy (Basel), 2024)
Herbicides are important for weed control but can severely impact ecosystems, causing soil and water contamination, biodiversity loss, and harm to non-target organisms. Tebuthiuron, widely used in sugarcane cultivation, is highly soluble and persistent, posing significant environmental risks. Microbial inoculation has emerged as a sustainable strategy to mitigate such damage. This study investigated the phytoremediation potential of Mucuna pruriens and Canavalia ensiformis in tebuthiuron-contaminated soils, enhanced by fungal and bacterial inoculants. Crotalaria juncea served as a bioindicator plant, and Lactuca sativa was used in ecotoxicological bioassays. During a 140-day greenhouse experiment from September 2021 to March 2022, M. pruriens showed faster growth than C. ensiformis in uncontaminated soils but was more affected by tebuthiuron. Bacterial inoculants improved M. pruriens growth under stress, while fungal inoculants mitigated tebuthiuron’s effects on C. ensiformis. C. juncea exhibited high sensitivity to tebuthiuron but grew beyond 100 cm with bacterial inoculants. Ecotoxicological assays showed that bacterial bioaugmentation significantly reduced soil toxicity. Natural attenuation further decreased tebuthiuron toxicity, and prior cultivation of M. pruriens enhanced soil detoxification. This integrated approach combining phytoremediation and bioaugmentation offers a sustainable method to degrade tebuthiuron, foster safer agriculture, and reduce environmental and health risks.